2006
DOI: 10.1103/physrevb.73.224528
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al doping on the critical fields and gap values in magnesium diboride single crystals

Abstract: The lower (Hc1) and upper (Hc2) critical fields of Mg1−xAlxB2 single crystals (for x = 0, 0.1 and 0.2) have been deduced from specific heat and local magnetization measurements, respectively. We show that Hc1 and Hc2 are both decreasing with increasing doping content. The corresponding anisotropy parameter ΓH c2 (0) = H Very similar values have also been obtained by point contact spectroscopy measurements. The evolution of those gaps with Al concentration suggests that both band filling and interband scatterin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
(33 reference statements)
6
37
1
Order By: Relevance
“…On the one hand, ⌬ appears to be nearly constant or slightly increasing for lowdoping levels up to 10% Al and decreasing for higher doping as suggested by specific heat, point contact and scanning tunneling measurements on single and polycrystals. 14,24,25,27 On the other hand, specific heat and point contact data indicate a monotonic decrease in ⌬ with decreasing T c . 26,31,32 Moreover, in radiation damaged and disordered MgB 2 thin films monotonically increasing or weakly affected values of ⌬ were found by scanning tunneling measurements.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the one hand, ⌬ appears to be nearly constant or slightly increasing for lowdoping levels up to 10% Al and decreasing for higher doping as suggested by specific heat, point contact and scanning tunneling measurements on single and polycrystals. 14,24,25,27 On the other hand, specific heat and point contact data indicate a monotonic decrease in ⌬ with decreasing T c . 26,31,32 Moreover, in radiation damaged and disordered MgB 2 thin films monotonically increasing or weakly affected values of ⌬ were found by scanning tunneling measurements.…”
Section: Introductionmentioning
confidence: 90%
“…The dependence of both energy gaps on T c , i.e., doping level, has been measured by means of various techniques in different Al doped MgB 2 samples: specific heat of polycrystals, 14 point contact spectroscopy ͑PCS͒ and point contact Andreev reflection ͑PCAR͒ on single and polycrystals, [24][25][26] and scanning tunneling spectroscopy ͑STS͒ on single crystals. 27 Polycrystals and thin films of undoped MgB 2 damaged with neutron irradiation have also been studied by specific heat measurements and STS.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some scatter to the data, the trends clearly indicate a near linear suppression of ∆ σ . In contrast, no evidence is seen for such an enhancement in ∆ π for either of the polycrystalline reports [75,76] . The single -crystal data of Gonnelli et al .…”
Section: Superconducting Gaps In Mg 1 − X Al X Bmentioning
confidence: 77%
“…Whereas the T c of this Mg(B .9 C .1 ) 2 sample was approximately 22 K, it still showed a clear two -gap signature in its temperaturedependent specifi c heat [82] , and later tunneling studies clearly showed the continued existence of two gaps, even with this nearly 50% reduction in T c [84] . [75,76] . [74] .…”
Section: Mg(b 1 − X C X )mentioning
confidence: 99%
“…Flux line properties of aluminium substituted MgB 2 have been measured by several groups. [178][179][180][181][182] Essentially, the magnetic measurements in Mg 1Àx Al x B 2 display similar flux lattice properties as in pristine MgB 2 . The critical temperature, the anisotropy and the upper critical field are diminished as aluminium content increases.…”
Section: Aluminium Substituted Single Crystalsmentioning
confidence: 99%